Understanding the cultural environment of the outpatient care setting for patients with dementia receiving cancer treatment: A qualitative study - Naomi Farrington; Katherine Dantanus; Alison Richardson; Jackie Bridges (Wiley, 2023)
Abstract Introduction People with dementia have poorer cancer outcomes than those without dementia, and experience inequalities in access to, and quality of, care. Outpatient environments, where radiotherapy, chemotherapy and immunotherapy cancer treatments typically take place, have largely been excluded from research. This study was conducted to understand provision of treatment and support and experiences of care for people with dementia undergoing cancer treatment in the outpatient setting. Materials and Methods Using observation, interviews and document analysis, data were collected to scrutinize the cultural environment of ambulatory care, comprising the physical fabric of the care setting; interactions, behaviours and perceptions of those in the care setting; and the organizational, clinical and interactional processes involved in care delivery. The study was conducted in the outpatient oncology departments of two large teaching hospitals in England between January 2019 and July 2021. Results Data were gathered from a wide range of sources, including 15 h of observation, and interviews with patients (n = 2), caregivers (n = 7) and staff (n = 20). Evidence from this study suggests that the cultural environment of the outpatient care setting reflects and supports the standardized processing of people for cancer treatment. Dementia introduces a wider set of care requirements not catered for by this standardized treatment model and associated processes. Data showed that the needs of patients with dementia could be addressed most effectively when individualized care, as opposed to standardized care, was offered. Conclusion There is work to be done in outpatient cancer services to ensure responsiveness to individual patient need. This could be achieved by having an established way (or ways) of eliciting needs, preferences and expectations, a belief that a person's needs and expectations are legitimate and that effort should be made to address them, with the ability to accommodate these needs and expectations. Patient or Public Contribution Patients and caregivers were involved in the study design and development of study materials including the interview topic guide. They also assisted with discussion and clarification of study findings.